The first case of traumatic internal carotid arterial dissection?: Verneuil's case report from 1872 - Grond-Ginsbach, Caspar; Meisenbacher, Katrin; Böckler, Dittmar; Leys, Didier (Revue neurologique, 2021)
Dissecting aneurysms of the internal carotid artery were considered as very rare disorders before the seventies. Undiagnosed carotid-artery dissections, however, may have gone hidden behind earlier reports of delayed “apoplexy” due to “traumatic carotid thrombosis”. Here, we present a case report of delayed stroke after trauma, published by Aristide Verneuil in 1872 in the Bulletin de l’Académie de Médecine and cited under the heading of vascular rupture and dissecting aneurysm by Heinrich Quincke in 1876. Verneuil's case report represents, to our knowledge, the first detailed clinical description of a patient with a traumatic carotid dissection confirmed at autopsy. The author highlighted the diagnostic challenges of this case, head injury followed by delayed hemiplegia suggesting an intracranial bleeding.